SPATIAL TEMPORAL VARIATION OF LAND SURFACE TEMPERATURE IN AMBON CITY CENTER AREA - Rakuasa, Heinrich; Budnikov, Viktor Vladimirov; Rifai, Ahmat; Latue, Philia Christi (Jurusan Pendidikan MIPA FKIP Universitas Pattimura, 2024)
Land use change from vegetation to built-up land in Ambon City Center affects the increase of land surface temperature and creates the urban heat island phenomenon, which has the potential to affect local and global climate. The method used in this research is the analysis of Landsat 8 satellite images through Google Earth Engine (GEE), which enables efficient and accurate data processing. The analysis shows that the highest surface temperature in the region increases from 27.35°C in 2015 to 29.30°C in 2025, while the lowest temperature also increases. These findings confirm the need for attention to sustainable spatial management strategies to reduce the negative impacts of urbanization, maintain environmental quality, and improve the quality of life of people in Ambon City